Can Hisense computer-assisted surgery system (Hisense CAS) improve anatomy teaching in pediatric liver surgery? - Liu, Jie; Xiu, Wenli; Lin, Aiqin; Duan, Guangqi; Jiang, Nannan; Wang, Bao; Wang, Feifei; Dong, Qian; Xia, Nan (Surgical and radiologic anatomy (English ed.), 2024)
Purpose This study aimed to investigate the effectiveness of the Hisense computer-assisted surgery system (CAS) in teaching pediatric liver surgical anatomy. Methods The research subjects were residents who underwent standardized training at the Department of Pediatric Surgery at Yijishan Hospital of Wannan Medical College from May 2022 to May 2023. Results The study recruited a total of 62 students, with 31 students assigned to the Hisense CAS group (12 males and 19 females) and the remaining 31 students serving as controls (Control group, 15 males and 16 females). There were no significant differences in baseline characteristics observed between the two groups. This study found that the average scores of the Hisense CAS teaching group in the liver surgery evaluations were higher than those of the control group. Specifically, the Hisense CAS group had an average score of 84.25 ± 5.70 points in the liver surgery knowledge test, 77.10 ± 8.12 points in the image reading test, and 70.58 ± 8.79 points in the surgical simulation test, while the traditional teaching group had average scores of 73.45 ± 6.12 points, 69.81 ± 6.05 points, and 66.42 ± 6.61 points, respectively; the differences between the two groups were statistically significant ( P < 0.05). Furthermore, this study also found that the Hisense CAS teaching model resulted in significantly better teaching satisfaction on the part of the residents in terms of standardized teaching for physicians in pediatric liver surgical anatomy. Conclusion In conclusion, this study demonstrated greater satisfaction of the residents with the use of 3D reconstruction added to traditional teaching sessions and better performance during the posttraining evaluation.